2004
DOI: 10.1111/j.1365-2249.2004.02549.x
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of human milk cells: persistent high expression of osteopontin during the lactation period

Abstract: SUMMARYTo continue the search for immunological roles of breast milk, cDNA microarray analysis on cytokines and growth factors was performed for human milk cells. Among the 240 cytokine-related genes, osteopontin (OPN) gene ranked top of the expression. Real-time PCR revealed that the OPN mRNA levels in colostrum cells were approximately 100 times higher than those in PHA-stimulated peripheral blood mononuclear cells (PBMNCs), and 10 000 times higher than those in PB CD14+ cells. The median levels of OPN mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 43 publications
(48 reference statements)
2
51
1
1
Order By: Relevance
“…The role of OPN in mammary gland development and lactation has been confirmed using a transgenic mouse model expressing OPN antisense RNA in the mammary gland (Nemir et al, 2000). The presence of OPN in milk and the high expression in mammary gland epithelial cells may account for the proliferation and differentiation of mammary glands (Nagatomo et al, 2004). Osteopontin gene exhibits a moderate level of sequence conservation (Crivello and Delvin, 1992).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The role of OPN in mammary gland development and lactation has been confirmed using a transgenic mouse model expressing OPN antisense RNA in the mammary gland (Nemir et al, 2000). The presence of OPN in milk and the high expression in mammary gland epithelial cells may account for the proliferation and differentiation of mammary glands (Nagatomo et al, 2004). Osteopontin gene exhibits a moderate level of sequence conservation (Crivello and Delvin, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…The protein is found in milk, plasma and urine. Nagatomo et al (2004) reported that both mRNA and protein levels were highly expressed during lactation and thus seem to have an effect on milk production traits. The OPN has been assigned several roles like binding to the cells via GRGDS, extracellular matrix components, regulation of formation and remodeling of mineralized tissue, recruiting and stimulating macrophages in response to infection and interactions with Ca 11 ions (Denhardt and Guo, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, certain molecules, such as osteopontin and CD44 (a cell surface transmembrane glycoprotein) can, via alternatively spliced or glycosylated isoforms, mediate completely different interactions among separate cell lineages in different tissues and organs. Thus, osteopontin plays a role in lactation [19,20], bone morphogenesis, wound healing [21], signaling between gonadotrophs and other cell populations in the pituitary [22], and other processes, whilst CD44 is involved in lymphocyte homing to lymph nodes, epithelial cell adhesion to the substratum, hemopoiesis and macrophage activation amongst many other roles [reviewed in [23]]. Hence, the structure and behavior of tissues composing normal organs depends upon integrated parallel and serial communications between differing organ cell populations and the messengers and receptors involved in these signals can vary, depending upon the identities of the living players in a specific context at a given time.…”
Section: I) Embryological Organ Formationmentioning
confidence: 99%
“…In human milk, OPN were highly expressed at both mRNA and protein levels during lactation (Nagatomo et al, 2004), and studies proposed that it might be useful in preventing rotavirus infections during lactating period (Naficy et al, 1999 …”
Section: Introductionmentioning
confidence: 99%